Cognitive Behavioral Therapy for Insomnia in Breast Cancer Survivors: A Review of the Literature - Aricò, Debora; Raggi, Alberto; Ferri, Raffaele (Frontiers in Psychology, 2016)
Background: Insomnia is a common sleep disorder in patients with breast cancer and studies show a higher frequency than in the general population but it appears to be understudied and the treatment seems to be a neglected problem. There is a growing body of evidence about the efficacy of cognitive behavioral therapy for insomnia (CBT-I) in breast cancer survivors. The aim of this review is to examine the best available scientific evidence related to CBT-I and insomnia in patients with breast cancer and to assess the effect of CBT-I on their psychosocial functioning, sleep, quality of life, and mood. Methods: Empirical articles published in peer-reviewed journals from the earliest reports available until August 2015 were considered. The research on PubMed generated 18 papers, three of which did not meet the inclusion criteria. Another paper was retrieved by screening the reference list of the previously selected papers. Results: A total of 16 studies were found that evaluated the effects of CBT-I in breast cancer patients. CBT-I appears to be an effective therapy for insomnia in breast cancer survivors, improving mood, general and physical fatigue and global and cognitive dimensions of quality of life. CBT-I may also reduce menopausal symptoms, such as hot flushes and night sweat problems, frequency of medicated nights, level of depression, and anxiety. Conclusions: CBT-I seems to be an eligible intervention for improving sleep in breast cancer survivors. Improvements concerning insomnia and sleep quality are durable (usually up to 12 months) and statistically significant.